EGLĖ RINDZEVIČIŪTĖ, The Will to Predict: Orchestrating the Future through Science, Ithaca and London 2023, Cornell University Press, 306 p., ISBN 9781501769771 - Studený, Luboš (Dějiny – teorie – kritika, 2024)
Recenze